4(a+7)-2a=a-3

Simple and best practice solution for 4(a+7)-2a=a-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(a+7)-2a=a-3 equation:


Simplifying
4(a + 7) + -2a = a + -3

Reorder the terms:
4(7 + a) + -2a = a + -3
(7 * 4 + a * 4) + -2a = a + -3
(28 + 4a) + -2a = a + -3

Combine like terms: 4a + -2a = 2a
28 + 2a = a + -3

Reorder the terms:
28 + 2a = -3 + a

Solving
28 + 2a = -3 + a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1a' to each side of the equation.
28 + 2a + -1a = -3 + a + -1a

Combine like terms: 2a + -1a = 1a
28 + 1a = -3 + a + -1a

Combine like terms: a + -1a = 0
28 + 1a = -3 + 0
28 + 1a = -3

Add '-28' to each side of the equation.
28 + -28 + 1a = -3 + -28

Combine like terms: 28 + -28 = 0
0 + 1a = -3 + -28
1a = -3 + -28

Combine like terms: -3 + -28 = -31
1a = -31

Divide each side by '1'.
a = -31

Simplifying
a = -31

See similar equations:

| 22x-8(2x-3)=50 | | 30+x=31 | | 5y-5=7+4(y-4) | | 8-5(a+2)=-6a+9 | | 15y+3+7x=180 | | 3x-18=-6x | | 4x-23=12x+53 | | 4x^2+72+324=0 | | 5p-(3p+p)=6p+1 | | 12x-2(4x+-4)=-24 | | ?8c+21=2c+1 | | 3x-4=8x+10 | | x+6(4)=18 | | 6x-2x-6=5 | | G^2-20g+10=0 | | -75-k=-92 | | 15x^4-30x^2+15x=0 | | -27+15x=33-15 | | x+(3x-22)=180 | | A=4tg(2x+1)+3tg(3x-1) | | 11x+49=0 | | ln(3)=8 | | 2+3(t+4)=11 | | 5y-28=6x | | 4x+5=-8x-7 | | .04x+8=24 | | 2(18-6y)-3y=-24 | | 9=3(k-1)+k | | y=cos(2y) | | 2l=21 | | 7x-112=0 | | 21=6n |

Equations solver categories